Wheat middlings in high concentrate rations: digestibility and ruminal metabolism - Dalke, B.S.; Bolsen, K.K.; Sonon, R.N. Jr.; Young, Matthew A. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Six medium-framed steers, fitted with ruminal cannulae were used in a 6 × 6 Latin square design and fed the following six high concentrat e (90%) rations: control; 5, 10, or 15% pelleted wheat middlings (WM) replacing the concentrate (dry rolled corn); and 5 or 10% pelleted WM replacing the roughage (chopped alfalfa hay). Dry matter (DM), organic matter (OM), and starch digestibilities decreased linearly when increasing levels of WM replaced the concentrate , but replacing the roughage increased DM and OM digestibilities linearly. WM could replace only up to 5 % of the concentrate without reducing nutrient digestibilities, but complete (10% WM) replacement of the roughage increased nutrient digestibilities.
Keywords: Beef; Wheat middlings; Beef cattle; Feedlot; Digestibility